2012
DOI: 10.1371/journal.pone.0044263
|View full text |Cite
|
Sign up to set email alerts
|

Polar/Ionizable Residues in Transmembrane Segments: Effects on Helix-Helix Packing

Abstract: The vast majority of membrane proteins are anchored to biological membranes through hydrophobic α-helices. Sequence analysis of high-resolution membrane protein structures show that ionizable amino acid residues are present in transmembrane (TM) helices, often with a functional and/or structural role. Here, using as scaffold the hydrophobic TM domain of the model membrane protein glycophorin A (GpA), we address the consequences of replacing specific residues by ionizable amino acids on TM helix insertion and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 44 publications
1
32
0
Order By: Relevance
“…Thus, multiple contacts are important for the pilin-PilS interaction. Rare charged residues in TM segments are typically buried within multi-TM proteins or involved in protein-protein interactions (48,49). PilA E5K or PilS R24E substitutions disrupted PilA-PilS interactions and dysregulated PilA expression, but the PilA E5K and PilS R24E charged-swapped pair failed to interact (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, multiple contacts are important for the pilin-PilS interaction. Rare charged residues in TM segments are typically buried within multi-TM proteins or involved in protein-protein interactions (48,49). PilA E5K or PilS R24E substitutions disrupted PilA-PilS interactions and dysregulated PilA expression, but the PilA E5K and PilS R24E charged-swapped pair failed to interact (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…30 Although hydrophobic interactions between TM segments are more abundant, hydrogen bonding or salt-bridge formation between membrane-spanning charged residues is essential to drive membrane protein folding while, at the same time, reducing the unfavorable energetics of inserting charged residues into the membrane. 31 Hence, interactions between polar residues in adjacent TM segments have been shown to favor membrane insertion. [32][33][34] PV 2B comprises two TM segments harboring conserved charged residues.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the presence of charged amino acid residues (lysine, arginine) in the CP sequence suggests that incorporation of the CP into the membrane might be energetically unfavorable. However, Bano-Polo et al [51] showed that for the GpA trans-membrane sequence, replacement of nonpolar residues with polar residues (including lysine and arginine) did not hinder dimerization of the protein and its insertion into hydrophobic environment when these residues pointed to the lipid facing interface. However, point mutations at residues located at the helix-helix interface abolished dimerization.…”
Section: Discussionmentioning
confidence: 99%